Report of the Seventy-eighth International Meeting of the Catholic Biblical Association of America. (Catholic Biblical Quarterly, 2015)
The article discusses the highlights of the 78th International Meeting of the Catholic Biblical Association of America held at the Xavier University of Louisiana in New Orleans, Louisiana on August 1-4, 2015. Topics cited include a panel discussion on the topic "Scholarship and Social Engagement", the creation of task forces involving core group members in attendance and seminars conducted to discuss various religious topics. It discusses the presentation of research papers.